Industrial training report at Mutiara Furniture Sdn Bhd / Mohamad Akmal Hamizan Abdul Razak - Abdul Razak, Mohamad Akmal Hamizan (Faculty of Business and Management, 2023)
On 1 st March 2023, I started my industrial training as company clerk at Mutiara Furniture Sdn Bhd. I did my internship in this company for 6 months and only assigned in office department as a clerk. I find this company can be beneficial for me because its facilities with great location where I can gain experiences to study more about this industry. I have ended my internship on 15 th August successfully. Even though I was there as a trainee, that is not an excuse for a student not to work as areal staff in the office. We are given this opportunity to study more about how the real office environment work and its process in handling and manage office system management. As a trainee, there will have a lot of challenges to work with other people that we have never working with before so it is important to know how to handle problems in any situation and work under pressure. This company may be beneficial for me because from my observation, there is a lot of potential for this company to grow up and expand their business in this industry, so there will be a lot of chances for me to learn more and to boost the company sales and income. Moreover, I will also explain regarding my portfolio, detail of this company, all the training and experiences that I have gain, all SWOT analysis that I have observed in this company and all-important points and elaboration will be explain more in this report. At the last part of this report, I will discuss and suggest few recommendations to improve weaknesses in this company and I will end this repost with summarizing all of this report in conclusion.